PENGARUH KUALITAS PRODUK DAN PERSEPSI RESIKO TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE TOKOPEDIA PADA MASYARAKAT KOTA BATAM - Saragih, Pandapotan Saragih; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2023)
This study aims to observe and analyze the associations experienced with variables, product quality and risk perception in Tokopedia E-commerce shopping decisions for residents of Batam City. This study uses a quantitative descriptive method. The data collection was carried out by distributing questionnaires to a total of respondents in which the respondents were residents of Taman Anugrah Housing Rt/Rw 001/015 Tembesi Village, Sagulung District, Batam City, a total of 156 respondents. Using the SPSS tool version 26. set on randome sampling technique. Through statistical tests it was observed if the variable product quality and risk perception were normally distributed. Through the acquisition of the t test shows if the product quality variable has a significant impact on the purchase decision as well as the risk perception variable has a significant impact on the purchase decision. but the results of the f test with others say that the variable product quality and risk perception have a positive and significant impact on Tokopedia E-commerce shopping decisions for residents of Batam City. Keywords: Product Quality; Perceived Risk; Purchase Decision.